Policy success: What is the role of implementation support programmes?. (16th September 2021) - Peckham, Stephen; Hudson, Bob; Hunter, David; Redgate, Sam
Abstract: The policy implementation process is often overlooked when policy is introduced potentially leading to policy failure. This is particularly relevant in complex policy areas where there is a lack of collaborative policy‐making and where implementation is in dispersed governance. This paper discusses the findings of a study examining a novel policy implementation support programme developed by the English Department of Health for the Care Act 2014, the most significant changes to the provision of social care for 60 years. Given the complexity of the changes, the Department of Health and its key partners introduced an Implementation Support Programme to increase the likelihood of effective implementation. As part of a suite of research studies, we examined the effectiveness of the implementation support programme in helping local authorities, responsible for social care delivery, implement the key Care Act priorities. We found that the support programme was effective in supporting 'implementation readiness' particular in situations where the context and policy itself are complex. We found that while important for the delivery of policy, such support programmes do not necessarily in themselves guarantee successful implementation. However, future evaluations of policy should include examining how the implementation is, or is not supported, in order to fully understand reasons for policy success and failure.